Delayed liver regeneration in C3H/HeJ mice: possible involvement of haemodynamic and structural changes in the hepatic microcirculation - Marlini Muhamad; Mohd Hairulhisyam Ngatiman; Mabuchi A.; Mallard B.L.; Akashi-Takamura S.; Harper J.L.; Wheatley A.M. (Blackwell Publishing Ltd, 2024)
Indexed by Scopus/WOS